KORELASI FAKTOR DEMOGRAFI LANSIA DENGAN KECEMASAN KEJADIAN COVID-19 DI KECAMATAN ENDE TENGAH KABUPATEN ENDE PROVINSI NUSA TENGGARA TIMUR - Syaputra Artama; Khrispina Owa (2022)
Health services during the pandemic have faced many challenges with the increase in COVID-19 cases among the elderly. The high number of cases has a negative impact on the mental health of the elderly. The anxiety about the incidence of COVID-19 is a mental health problem for the elderly. Efforts to overcome anxiety can have a positive impact on improving health and quality of life. This study aims to determine the correlation of demographic factors of the elderly with the quality and anxiety of covid-19 events. The research method used was correlational with a sample of 100 respondents and sampling was carried out by consecutive sampling from February 2022 to May 2022. Data analysis using spearman test. The results of the study obtained the correlation value of respondents' demographic factors with anxiety of COVID-19 events, namely the value of p = 0.019 (age factor), p = 0.019 (sex factor), p = 0.019 (education level), p = 0.019 (marital status) and p = 0.019 (employment status). From these results, the p value of > 0.05 indicates the absence of a relationship between demographic factors (age, gender, education level, marital status, and occupation) of respondents with anxiety of COVID-19 events. The correlation values obtained from age factors -0.035, sex -0.017, marital status -0.055, and occupation -0.118. Demographic factors have a very weak strength of relationships with negative correlations. The conclusion that it is important to always provide physical, emotional and psychological support for the elderly without looking at the demographic aspects and characteristics of the elderly and recommendations for the elderly to do positive things related to physical and mental health so that the quality of life of the elderly is increasing.